Trends in Gender Authorship and Collaborations: A 30-Year Comparative Bibliometric Analysis of Manuscripts from The Journal of Bone and Joint Surgery and The Bone and Joint Journal - Maria E. Squire; Katherine Schultz; Donnell McDonald; Cory Meixner; Dayton Snyder; Alyssa M. Cooke; Jacob C. Davis; Sarina Masso Maldonado; Carlos R. Martinez Licha; Elizabeth C. Whipple; Melissa A. Kacena; Randall T. Loder (Scientifica)
Publishing original peer-reviewed research is essential for advancement through all career stages. Fewer women than men hold senior-level positions in academic medicine and, therefore, examining publication trends relative to gender is important. The goal of this study was to examine and compare publication trends in The Journal of Bone and Joint Surgery (JBJS) and The Bone and Joint Journal (BJJ) with a particular emphasis on trends regarding author gender. Data was collected and analyzed for manuscripts published in JBJS and BJJ over the past 30 years. For manuscripts published in 1986, 1996, 2006, and 2016, we recorded the numbers of authors, manuscript pages, references, collaborating institutions, the position in the byline of the corresponding author, the country of the corresponding author, and the names of the first and corresponding author. We also calculated the normalized number of citations and corresponding author position. The number of authors, institutions, and countries collaborating on manuscripts published in both JBJS and BJJ increased over time. JBJS published more manuscripts from North America and BJJ published more manuscripts from Europe. In both journals, the percentage of women as first and/or corresponding author increased over time. Trends over the past 30 years have shown increased collaborations with greater citations in manuscripts published in JBJS and BJJ. In the same time period, both journals demonstrated a rise in the percentage of manuscripts with women first and/or corresponding authors, suggesting a decrease in the gender gap.